2012
DOI: 10.1515/jpem-2012-0117
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis nigricans predicts the clustering of metabolic syndrome components in Hispanic elementary school-aged children

Abstract: Background Acanthosis nigricans (AN) is a dermatologic condition associated with hyperinsulinemia, a marker of insulin resistance that is the principal abnormality in metabolic syndrome (MetS). We examined the association of AN with the clustering of MetS components. Methods A cross-sectional study was conducted in an urban school-based health center in New Mexico. Students without diabetes were evaluated for AN, a family history of type 2 diabetes, body mass index (BMI), and MetS components. The clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
4
6
0
1
Order By: Relevance
“…AN was common in our study population, with 63 % and 43% found to have AN and Severe AN respectively. There was a positive association between BMIz and presence of AN (with an increase of 1SD in BMI leading to a doubling in the risk of AN) consistent with other published studies of AN in adolescent groups (4)(5)(6). …”
supporting
confidence: 89%
See 1 more Smart Citation
“…AN was common in our study population, with 63 % and 43% found to have AN and Severe AN respectively. There was a positive association between BMIz and presence of AN (with an increase of 1SD in BMI leading to a doubling in the risk of AN) consistent with other published studies of AN in adolescent groups (4)(5)(6). …”
supporting
confidence: 89%
“…Studies have identified AN in adolescence as a marker for type 2 Diabetes Mellitus (DM) (2,3) and insulin resistance (IR)(4-7) yet it is unclear whether AN in adolescent obesity is associated with increased cardiovascular risk separately to risk for diabetes. Whilst attempts to identify cardiovascular risk by presence of AN in adolescents have been made using adult-based components of the metabolic syndrome, (6) (7) evidence for associations between AN and contemporary arterial pathological processes, such as arterial stiffening, has not been investigated. Pulse Wave Velocity (PWV), is a non-invasive proxy for arterial stiffness, demonstrated to be a reliable predictor of future cardiovascular mortality and morbidity in adults, (8,9) and shown to correlate with degree of atheroma in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, articles where the score calculated was non‐continuous ( n = 8) and articles where the score was measured at adolescence or adulthood ( n = 58) were excluded. A total of 91 articles met the review criteria and were included in the data extraction .…”
Section: Resultsmentioning
confidence: 99%
“…11 Another study examined the association of AN and metabolic syndrome and concluded that early intervention in children with AN can be beneficial in decreasing future health complications. 12 AN in childhood is associated with an increased risk of obesity, hypertension, hyperinsulinemia, insulin resistance, and type II diabetes. 9…”
Section: Childhood Obesity and Acanthosis Nigricansmentioning
confidence: 99%